RADI-12. LEPTOMENINGEAL FAILURE AFTER PREOPERATIVE VERSUS POSTOPERATIVE RADIOSURGERY. (12th August 2019) - Fiveash, John; Riley, Kristen; Markert, James; Guthrie, Bart; Foreman, Paul; Popple, Richard; Marcrom, Sam; Strickler, Scott; Willey, Christopher; McDonald, Andrew; Thomas, Evan; Stewart, John; et al.
Abstract: INTRODUCTION: Postoperative stereotactic radiosurgery (postop SRS) is potentially complicated by difficulty defining the target volume and the risk of leptomeningeal seeding at the time of surgery. It is hypothesized that preop SRS may render cells less viable to disseminate in the leptomeningeal space. This retrospective study compares the leptomeningeal dissemination (LMD) rate for preop versus postop radiosurgery METHODS: We identified 140 patients with brain metastases who underwent resection and radiosurgery at the University of Alabama at Birmingham including 91 postop patients (2005–2015) and 49 preop patients (2011–2018). The preop group included 19 patients enrolled in a phase I trial of preoperative radiosurgery (12–15 Gy) for tumors 2–6 cm in greatest diameter. In that study 15 Gy was found to be safe in the preop setting but further escalation was not attempted. An additional 30 patients received preop SRS off-study (median dose 15 Gy). The median postop dose was 16 Gy. LMD recurrence was defined as focal pachymeningeal or diffuse leptomeningeal enhancement of the brain, spinal cord, or cauda equina, dural enhancement beyond 5 mm from the index metastasis, subependymal enhancement, or enhancement of cranial nerves. This definition is not limited to carcinomatosis. All events were categorized and confirmed by at least two physicians. RESULTS: 40/140 (29%) patients developed new focal or diffuse LMD. Preop SRS was associated with a higher freedom from leptomeningeal recurrence (84% vs 60% at one year, p=0.021 Breslow, p=0.128 log-rank). Since later LMD may not be related to surgery, a second analysis censoring follow-up at one year was performed and confirmed this trend (p=0.008 Breslow, p=0.014 log-rank). CONCLUSIONS: Preoperative SRS is associated with a reduction in the risk of LMD compared to postop SRS. Focal pachymeningeal dissemination may not always be recognized as related to surgery. A randomized trial of preop vs postop SRS is warranted.